Maintenance management analysis of welding equipments in an agricultural machinery factory - Borges, David da Silva; Resende, André Alves de; Santos, Aline Gonçalves dos (Brazilian Journal of Production Engineering, 2023)
Maintenance management impacts several sectors of an organization, especially production. In factories where the welding process takes place, good maintenance management is important so that the equipment has the proper performance and does not negatively affect production. Given this context, the present work was developed with the aim of analyzing the maintenance process of the welding sector of an agricultural equipment factory to generate proposals for improvements. To this end, a participant research was developed, in which interviews were conducted with several employees of the organization who are involved in the maintenance and welding process. Data were collected through the organization’s database and an internal benchmarking was carried out. As a result, it was observed that the TPM (total productive maintenance) is not developed consistently in the analyzed sector and possible improvements were identified. Therefore, it is concluded that the analysis of total productive maintenance provides the identification of improvements for the organization